Soft Coral Epibiotic Bacteria Vibrio alginolyticus from Sarangani Bay, Mindanao Philippines as Potent Source of Antibacterial Agent (Indonesian Journal of Science and Technology, 2025)
This study aims to explore the antibacterial properties of the different epibiotic bacterial species thriving in the surface tissues of the soft corals, and their potential application in developing novel antibacterial agents. There were ten soft coral species randomly collected from Sarangani Bay in Mindanao, Philippines: 3 sarcophyton sp., two sinularia sp., 1 nepthia sp., 1 stenonephthya sp., 1 anthelia sp., 1 lithophyton sp. and 1 asteropicularia sp. All soft coral species collected harbored epibiotic bacteria. Fifteen epibiotic bacterial species were isolated and tested for antibacterial properties against Staphylococcus aureus (gram-positive) and Escherichia coli (gram-negative) as test organisms. Their respective zones of inhibition were compared to that of the commercial antibiotics Penicillin, Chloramphenicol, and Gentamycin (as positive controls). Results indicated varied antibacterial effects, with one isolate, Vibrio alginolyticus (EB6), showing significant activity, with the zone of inhibition of 9.33 mm against E. coli, comparable to that of Chloramphenicol and Gentamycin, with the zone of inhibition of 10 and 9 mm, respectively. These findings highlight the potential of marine-derived bacteria in developing new antibacterial agents.